The Use of The Task-Base Language Teaching (TBLT) Method to Improve Learning Outcomes of Arabic Language Skills - Kosim, Nanang; Ardiansyah, Ade Arip; Hikmah, Hilda Saripatul; Yusuf Ali Shaleh Atha (IAIN Madura, 2024)
This study was prepared with the aim of improving students' learning skills using the Task Base Language Teaching (TBLT) method for class VIII students of MTs Al-Hurriyyah Kutawaluya, Karawang. School year 2023/2024. Improving learning skills referred to in this study are istima' (listening), qira'ah (reading), kalam (speaking), and kitabah (writing) skills. This research is classroom action research (PTK), and its design uses the Kemmis and McTaggart model. This research was carried out salam 2 cycles in the even semester of the 2023/2024 school year, namely in May 2024. The subjects of this study were VIII grade students of MTs Al-Hurriyyah Kutawaluya, consisting of 25 students. Data collection techniques used observation and interviews, and the data were analyzed descriptively and presented in the form of tables and graphs. The results showed an increase in student learning skills, namely in cycle I by 73,25% (good category), then in cycle II, there was an increase, which amounted to 82,79% (very good category), and means that there is an increase; therefore, the use of the task-based language teaching (TBLT) method in Arabic language subjects can improve the learning skills of 8th-grade students of MTs Al-Hurriyyah Kutawaluya. This research supports the development of better Arabic learning strategies in Madrasah. Recommendations for future research: expand the variables and longitudinal design to understand the effects of TBLT in Arabic language teaching.